Binding technique on the ground in the study of the effects of man-caused accidents - Batiy, V.G.; Glebkin, S.I.; Kochnev, N.A.; Selyukova, V.V.; Prokhorets, S.I.; Fedorchenko, D.V.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2013)
The technique of determining the coordinates of the point of measuring device location during the researches in contaminated areas and near the radiation- and chemically-dangerous objects is proposed. It is shown the optimal way is the integrated usage of different methods: linear resection using laser range finders; tachymeters; GPS systems.